Facilitating epistemic fluency of undergraduate students during the interdisciplinary research process - van Lambalgen, Rianne M.; de Vos, Febe (Frontiers in Education, 2023)
Introduction In this article we show how students share knowledge when integrating disciplinary insights in an interdisciplinary research project. More specifically, this research looks at how students communicate to create a shared mental model during moderated sessions with use of CoNavigator as an interdisciplinary collaboration tool or Miro as an online mind map tool. The study focuses on the interdisciplinary capstone of the Liberal Arts and Sciences bachelor program at Utrecht University (LAS), where students collaborate in multidisciplinary groups by going through the interdisciplinary research process (IRP).This process asks students to define an interdisciplinary research question, to define disciplinary insights and combine each other’s disciplinary insights to create a more comprehensive understanding of their research question. The integration of disciplinary insights requires working with different perspectives and acknowledging uncertainty, thereby requiring epistemic fluency and higher modes of knowledge. This research looks at how a structured session with CoNavigator or Miro can help students use these processes when integrating insights. Methods Seven groups participated in this research, with whom we moderated a session using either CoNavigator or Miro at the start of the integration phase with the purpose of sharing disciplinary insights and finding common ground. We observed each group, looking at communication related to construction, constructive conflict and co-construction. In addition, we looked at evaluation of the tool immediately after the session and the assessment of the integration chapter of all groups. Results We found that each phase of the moderated session elicited different responses in terms of constructive conflict and co-construction, thereby helping students to actively work with different ways of knowing and to define and connect disciplinary differences. In their communication, students show examples of epistemic fluency and higher modes of knowledge, although this did not directly translate into a better assessment of their integration chapter. Discussion These results show that discussing disciplinary differences and finding common ground through a session with CoNavigator or Miro gives students a structured way to start with their interdisciplinary integration. We argue that LAS-students exhibit epistemic fluency when working with the tools, but also develop this throughout the session. It appears that the epistemic fluency students already possess prior to the IRP can be further developed by the epistemic fluency expressed by teammates during the tool session. The practice and development of epistemic fluency will always involve uncertainties, but facilitating interdisciplinary integration in this way is valuable as it provides an opportunity to work with these uncertainties and offer students space to speak and integrate freely.